APCB’s Abstracts 1: 9th Asian Pacific Congress on Bronchology and Interventional Pulmonology - Asia-Pacific Congress Bronchology-Interventional Pulmonology (The Interventionalist Journal, 2023)
APCB’s Abstracts 1 1. OP01: ROLE OF ULTRASONOGRAPHY IN THE ASSESSMENT OF PULMONARY FIBROSIS IN ILD AND ITS CORRELATION WITH HRCT AND CRYOBIOPSY 2. OP02: A STUDY OF CASES REQUIRING RE-TREATMENT SHORTLY AFTER RIGID BRONCHOSCOPIC THERAPY 3. OP03: EXTRACORPOREAL SUPPORT AS AN AID FOR COMPLEX CENTRAL AIRWAY OBSTRUCTION - A CASE SERIES 4. OP04: THE “HITCH-STITCH” FOR PREVENTING HIGH TRACHEAL STENTING MIGRATION 5. OP05: COMPARISION OF TRANSBRONCHIAL LUNG FORCEPS BIOPSY AND CRYOBIOPSY FOR DIAGNOSIS OF DIFFUSE PARENCHYMAL LUNG DISEASE- A PROSPECTIVE SINGLE CENTRE STUDY